The origin and evolution of copper patina colour. (15th August 2019) - Leygraf, C.; Chang, T.; Herting, G.; Odnevall Wallinder, I.
Graphical abstract: Highlights: Initial dark colour of exposed copper due to semiconducting properties of cuprite. At least 0.8 ± 0.2 μm cuprite thickness required to fully cover underlying copper. Subsequent green-blue colour due to colour forming Cu(II) in outer patina layer. At least 12 ± 2 μm outer patina thickness needed to fully cover inner cuprite layer. No significant influence of atmospheric environment on patina colour. Abstract: The copper patina colour has been systematically explored through a large set of short- and long-term exposed copper metal samples. The initial brown-black appearance is attributed to semiconducting properties of cuprite (Cu2 O) and fully attained at thickness 0.8 ± 0.2 μm. The characteristic green-blue appearance is due to the colour forming Cu(II)-ion in the outer patina layer which needs to be 12 ± 2 μm to fully cover the inner cuprite layer. No significant influence of atmospheric environment on patina colour is discerned. The green-blue patina colour on historic copper was attained after shorter exposures than in modern copper due to more inhomogeneous microstructure.